Analisis Dispersi Karbon Monoksida (CO) pada Udara Ambien di Simpang Tiga Pal Merah - Herawati, Peppy; Suzana, Asih; Ilham, M. (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to analyze CO concentration, CO concentration rate, and its distribution pattern in the Palmerah Three-Way Intersection area of Jambi City. The research method used is descriptive quantitative with measurements at three sampling points (Points I, II, and III) each 100 m from the Traffic Signal Device (APILL). The measurement results showed the highest CO concentration of 8,991 µg/Nm³ occurred at Point II on Tuesday Afternoon, Points II and III on Thursday Afternoon, and Points I and II on Saturday Afternoon. The lowest concentration was recorded at 2,247 µg/Nm³ at Point II on Tuesday Morning. These results indicate that traffic congestion contributes significantly to the increase in CO concentration in ambient air, so mitigation efforts such as traffic management and increasing green open spaces are needed to reduce the impact of air pollution in urban areas.